(untitled) (Revista de Investigaciones Universidad del Quindío, 2013)
In this work, preliminary results about the photocatalytic activity of ABO3 perovskite semiconductors of the type Pb1-xRxZr0,40Ti0,60O3 (R=La,Ba) are presented. The materials were prepared by the sol-gel method by varying x in the range 0, 0.5 and 1.0; complex, high-purity ceramic oxides were obtained with controlled stoichiometry. The materials were employed as active photocatalysts in the degradation of methylene blue, a contaminant frequently found in textile wastewaters. All the perovskites exhibited 80% of decolourization in the range of 120 min. The photocatalytic activity was favored by the presence of doping agents under UV irradiation.